2018
DOI: 10.1186/s12870-018-1533-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparative proteomic investigation of drought responses in foxtail millet

Abstract: BackgroundFoxtail millet (Setaria italica L. P. Beauv) has been considered as a tractable model crop in recent years due to its short growing cycle, lower amount of repetitive DNA, inbreeding nature, small diploid genome, and outstanding abiotic stress-tolerance characteristics. With modern agriculture facing various adversities, it’s urgent to dissect the mechanisms of how foxtail millet responds and adapts to drought and stress on the proteomic-level.ResultsIn this research, a total of 2474 differentially ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(39 citation statements)
references
References 59 publications
1
38
0
Order By: Relevance
“…Under drought stress, plant seedlings exhibit certain physiological and morphological variations [2,8], shown by leaf rolling and wilting [44,45], as well as the decreased RCW and wrinkled leaves (Figure 1a,d). Previous studies have demonstrated that drought stress also inhibits the photosynthesis of plants by affecting chlorophyll biosynthesis and facilitating stomatal closure [46,47], leading to the accumulation of MDA and ROS, which is harmful to the chloroplast photosystem II (PSII) [17,48].…”
Section: Morphological and Physiological Characteristics Related To Dmentioning
confidence: 99%
See 1 more Smart Citation
“…Under drought stress, plant seedlings exhibit certain physiological and morphological variations [2,8], shown by leaf rolling and wilting [44,45], as well as the decreased RCW and wrinkled leaves (Figure 1a,d). Previous studies have demonstrated that drought stress also inhibits the photosynthesis of plants by affecting chlorophyll biosynthesis and facilitating stomatal closure [46,47], leading to the accumulation of MDA and ROS, which is harmful to the chloroplast photosystem II (PSII) [17,48].…”
Section: Morphological and Physiological Characteristics Related To Dmentioning
confidence: 99%
“…Among the forms of environmental stress, drought stress has been considered as one of the major constraints in plant growth, survival, and production [1,2]. A lack of water not only disturbs photosynthesis, limits metabolic reactions, and inhibits CO 2 exchange, but also results in stress-related damage to chloroplasts [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Pearl millet is a stress tolerant crop and grows in the arid regions. Stress tolerance mechanisms associated with water deficit conditions were studied earlier in millets including pearl millet [52][53][54]. Based on high vapour pressure deficit and other studies related to drought, it has been inferred that these plants perform well under harsh conditions [54].…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 15% of mung bean proteins have not yet been extensively studied until now [1]. Recently, with the development of proteomic technique, label-free proteomics enables efficient and accurate identification and relative quantification of proteins, and it has been commonly used in plant proteomes research [9]. Plant peptides, whether they are extracellular or intracellular, have various physiological functions, such as signaling and defense [10].…”
Section: Introductionmentioning
confidence: 99%